2021
DOI: 10.1038/s41467-021-23047-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin-2 stabilizes adherens junctions and suppresses endothelial inflammation via modulation of β-catenin signaling

Abstract: Endothelial barrier integrity is ensured by the stability of the adherens junction (AJ) complexes comprised of vascular endothelial (VE)-cadherin as well as accessory proteins such as β-catenin and p120-catenin. Disruption of the endothelial barrier due to disassembly of AJs results in tissue edema and the influx of inflammatory cells. Using three-dimensional structured illumination microscopy, we observe that the mitochondrial protein Mitofusin-2 (Mfn2) co-localizes at the plasma membrane with VE-cadherin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Mfn2 localized at the mitochondrial outer membrane is a primary mediator of mitochondrial fusion events. Moreover, Mfn2 is also found at the plasma membrane where it serves a non-canonical function as a stabilizer of endothelial adherens junctions (AJs) [ 39 ]. To investigate if Mfn2 localizes to the plasma membrane in breast cancer MDA-MB-231 cells, we labeled cells with the plasma membrane dye MemBrite® Fix, which accumulates in the plasma membrane and withstands fixation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mfn2 localized at the mitochondrial outer membrane is a primary mediator of mitochondrial fusion events. Moreover, Mfn2 is also found at the plasma membrane where it serves a non-canonical function as a stabilizer of endothelial adherens junctions (AJs) [ 39 ]. To investigate if Mfn2 localizes to the plasma membrane in breast cancer MDA-MB-231 cells, we labeled cells with the plasma membrane dye MemBrite® Fix, which accumulates in the plasma membrane and withstands fixation.…”
Section: Resultsmentioning
confidence: 99%
“…Mfn2 was previously shown to be present at the plasma membrane where it plays a role in the stabilization of adherens junctions (AJs) [ 39 ] in endothelial cells. Our study provides additional evidence that Mfn2 is present at the plasma membrane in breast cancer cells and that expression of Cav-1 and its phosphorylation status are critical determinants of Mfn2 plasma membrane localization.…”
Section: Discussionmentioning
confidence: 99%
“…MFN2 promotes the NSC differentiation of hiPSCs by activating the Wnt/β-catenin signaling pathway [ 18 ]. Recent studies have shown that depletion of MFN2 in endothelial cells leads to inhibition of β-catenin sulfenylation, thereby activating the activity of the Wnt/β-catenin signaling pathway [ 19 ]. Therefore, we focused on the Wnt/β-catenin signaling pathway in the next section.…”
Section: Resultsmentioning
confidence: 99%
“…Although MFN2 is mainly located in the cytoplasm and mitochondria, both MFN2 and β-catenin can accumulate in the nucleus. Depletion of MFN2 leads to inhibition of β-catenin sulfenylation, thereby activating the transcriptional activity of β-catenin [ 19 ]. Similarly, our results showed that MFN2 can bind to β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of inflammatory signaling by cytokines such as interleukin-1β can downregulate the endothelial adherens junction protein VE-cadherin ( 39 ), which causes a loss of lung endothelial barrier integrity. The breakdown of endothelial adherens junctions in turn amplifies lung inflammation ( 40 ) thus creating a vicious cycle of lung endothelial barrier breakdown and inflammation.…”
Section: Sars-cov-2 and Lung Injurymentioning
confidence: 99%